Detection of toxin-associated genes in seven spa-types of Staphylococcus aureus in Iraq - Samarah Jafar Alwash; Rasmiya Abed Aburesha (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Staphylococci frequently cause opportunistic infections in patients with underlying disease, such as those with prosthetic devices, surgical patients, and patients with diabetes or individuals undergoing dialysis. Consequently, detecting the toxin-associated genes in different S. aureus strains, isolated from patients with wound and burn injuries and their environments, is essential to monitor and prevent the complication in such cases.Methods: Identification ofS. aureus that isolated from burn and wound injuries has been done according to the biochemical tests, then Spa-typing method was used to diagnose at the strain level. Toxin-associated genes, enterotoxin gene(sea, seb),exfoliative gene(eta), toxic shock syndrome gene(tst), and pantonevalentine leukocidin(pvl), were detected by polymerase chain reaction (PCR) method.Results: Two isolates were harboring tstand a single isolate harbored pvl, at the time that no isolates were foundetaandsebpositive among 19 S.aureus. While sea was the predominant toxin-associate gene in the studied S. aureus strains, it was detected in 13 isolates.Conclusion: Distribution of specific spa-type/sea-positive in diabetic foot ulcers at hospitals, indicating the poor sanitization conditions at Iraqi wound wards, and it is recommended to take swabs from the patients and their environments as a routine procedure